Instructional Design and Student Learning in Professional Legal Education - Julie Macfarlane; Pat Boyle (Legal Education Review)
The study which is described in this paper was designed with two complementary objectives in mind. The first objective was to carry out research to discover more about student conceptions of their learning in an educational program which would introduce a new approach to learning and challenge their expectations. The researchers — an instructional evaluation specialist and a law teacher — were particularly concerned in the first stage to explore as wide a range of student conceptions and reactions to the learning process as possible and then to attempt to draw some general observations from those results. A phenomenographic1 approach was used to leave open the possibility of discovering unintended and unexpected outcomes. The phenomenographic approach focuses on “mapping the qualitatively different ways in which people experience, conceptualise, perceive and understand various aspects of and phenomena in the world around them.” To this end, the researchers sought from student respondents as wide a range as possible of personal responses and reactions to their learning experiences and environment. The second objective of the study was to consider the question whether or not the design principles of the new program achieved their intended outcomes. These design principles and their anticipated implications for student learning described in detail below. The second objective of the project was therefore to provide information for decision-makers3 with which to evaluate the success of the new program in achieving its stated goals (including intended processes) and on which to ground program revisions and modifications for the second year of operation. These two drivers for the study provided a dual motivation to explore the impact of this new program on a sample of its first year student entrants. In order to ensure that the research results from the project could be meaningful and usefully translated into evaluative judgements about the success of the program in meeting its goals, three working hypotheses were formulated which were used to guide the data-gathering phase of the project; that is, face-to-face interviews conducted with the students. The three working hypotheses were derived from the design principles of the new program and knowledge of the students’ previous educational experiences and approaches to learning. The design principles of the program and the working hypotheses themselves are discussed in detail below. The empirical stage of the study took the form of a set of one-on-one interviews with a sample group of students from the new program, just three months into the program. The methodology used for these interviews, the working hypotheses which guided them and an analysis of the data derived follow below.